Odontogenic fungus maxillary sinusitis. Report of a clinical case (Эндодонтия Today)
In a 21-year-old woman, a sinusitis maxillaris resulting from overextension of root canal filling material after an endodontic treatment of a maxillary molar could be diagnosed through computed tomography. Root canal filling materials containing zinc oxide may cause aspergillosis of the maxillary sinus because they encounter growth of Aspergillus species. In case of maxillary sinusitis, surgical removal of overextended root canal filling material from the maxillary sinus is indicated. Dentists should be as careful as possible when treating maxillary teeth to avoid perforating the maxillary sinus floor; the use of zinc-free endodontic materials.